Exploring staff and procedural factors affecting patient safety in the operating room - Yahya Yahya; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi; Rahayu Nawangwulan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Patient safety in the operating room is a critical concern in healthcare delivery. While the Surgical Safety Checklist (SSC) improves safety outcomes, variability persists due to workforce characteristics, work motivation, and adherence to Standard Operating Procedures (SOP). Purpose: To examine associations between staff characteristics, motivation, and SOP compliance with patient safety quality in the operating room, and to identify the most influential factor. Method: A cross-sectional study of all 42 operating room healthcare workers (total sampling). Data were collected through Likert-scale questionnaires and analyzed using Chi-Square tests and multiple logistic regression. Results: Education level (p = 0.024), motivation (p = 0.000), and SOP compliance (p = 0.000) were significantly associated with patient safety quality. SOP compliance was the strongest determinant (OR = 234.770; p = 0.001). Conclusion: Adherence to SOP—especially the SSC—is the dominant factor influencing patient safety quality. Interventions should prioritize continuous SOP education, oversight, and cultivation of a robust patient safety culture.